Comparing the technical and individual possession statistics of academy players across different age groups in match-play - Emily Escreet; Steve Barrett; John Toner; John Iga; Christopher Towlson (PLoS ONE, 2025)
Background Youth soccer players in the UK transition into the professional game at 16 years of age. Understanding the differences between youth and professional standards can help coaches and clubs to support player development during this transition. Objectives To (i) assess the differences in technical and possession statistics between different age groups (U16, U18, U23) and outfield positions (central defender [CD], wide defender [WD], central midfielder [CM], attacking midfielder [AM], wide midfielder [WM], striker [ST]), within an English academy soccer programme, during match-play. Methods All matches were monitored using foot-mounted inertial measurements units (F-IMU; Playermaker™) to quantify the technical (touches and releases from the feet) and individual possession statistics (Time on the ball, Time on the ball per possession) from each match. Teams were instructed to play a 1-4-3-3 formation as part of their clubs playing philosophy, with positions defined per this formation. Data were analysed using a multi-variate ANOVA Two-tailed statistical significance was accepted as p ≤ 0.05 and measures of effect size were calculated using partial eta-squared (η2). Magnitude of the effect sizes were small (0.2<ES<0.6), moderate (0.6<ES<1.2), large (1.2<ES<2) and very large (≥2). Results Trivial to small effect sizes were observed across age groups for both technical and possession-based statistics during match-play. Across all age groups and positions, CD`s had the highest number of technical actions (touches and releases), whereas ST`s & AM`s, had the highest amount of time in possession of the ball. Further, positional analysis showed ST`s and AM`s had moderate to large decreases in time on the ball per possession at the U23’s age group in comparison to the U16 and U18’s, with no technical differences observed within the same positional analysis. Conclusion Attacking players (AM & ST) are required to move the ball quicker as they progress from U16 to U23’s within the current English football academy. Further exploration is required to assess if these changes are context specific given requirements of those age groups.